Qualidade do cuidado obstétrico e neonatal: avaliação de práticas em maternidades da rede cegonha cearense - Vidal, Eglidia Carla Figueiredo (2019)
The objective of this study was to evaluate the quality of obstetric and neonatal care in Ceará hospitals enabled in Rede Cegonha . Evaluative, exploratory and cross sectional study using the Quality Maternal Newborn Care m odel in its central component. Study developed in four maternity hospitals references in obstetric care in health macroregions in Ceará, with 440 puerperal women. Data collection instruments were used based on the quality standards of obstetric and neonata l care proposed by the World Health Organization . The evaluation involved five quality of care standards, five quality statements and 37 indicators. Data were collected between March 2017 and May 2018. Data were compiled and statistically analyzed using th e Statistical Package for Social Sciences® software, version 24.0. Exploratory analysis used Pearson's chi square, Fisher's exact, Likelihood Ratio for associations and logistic regression tests. Project approved by Research Ethics Committees. Of the patterns analyzed, the prevalence of adequacy was 32.1% in Evidence Based Practices for Routine Care, 14.5% in Effective Communication, 30.6% in Respect and Preservation of Dignity, 77.4% in Emotional support and 43.4% in competent and motivated human resources , with adaptation only in Emotional Support, globally. In comparisons between maternities, there was wide variation in most standards, whose adequacy in the standard Evidence based practices for routine care ranged from 1.1% to 53%, from zero percent to 53 .2% in the Effective Communication pattern, 10.8% to 38.3% in the Respect and Preservation of Dignity standard, 8.9% to 45% in the Emotional Support Standard, and 10.8% to 38.5% in the Competent and Motivated Human Resources standard. statistical differenc e between institutions in all standards. There was a correlation between women's satisfaction with quality of care and adequacy of care in three assessed patterns: care during childbirth, respect and privacy, and emotional support. Overall, there was no re lationship between the adequacy of the standard and women's satisfaction with the information and care received from professionals. It was concluded that there was a statistical difference in 28 of the 37 items evaluated and maternity 3 had a better overal l proportion in all patterns, while maternity 1 had a worse proportion. 16 indicators showed adequate quality of care with eight globally strengthened aspects: oxytocin in the prevention of postpartum hemorrhage; offering options for pain relief; breastfee ding in the first hour; exclusive breastfeeding until discharge; permission before examination or procedure; respect for religious and cultural needs; companion of choice of the woman; and satisfaction with the guidance offered to the companion. It was evidenced that the practices of maternal and neonatal care present a heterogeneity regarding the adequacy of the indicators. It is argued that maternal and neonatal care practices in women who had normal births in reference Stork Network maternity hospitals are consistent with the WHO Quality Standards, in line with the proposed paradigm shift with the Brazilian Stork Network.